Public Trust in the Religious Court to Handle Dispute of Sharia Economy - Erie Hariyanto (Universitas Islam Negeri Jakarta, 2022)
Religious court is not empowered to seek justice in settling sharia economic disputes. Practitioners of sharia economy lack the enthusiasm to demonstrate the importance of a religious court in solving sharia economic disputes. At the same time, Muslims have often utilized a religious court to solve problems in family law such as divorce, inheritance disputes, applications for child custody, probate, and grants. This trend indicates a lack of public trust in the religious court. This study analyzes how public trust is the main obstacle to improving religious court services to resolve sharia economic disputes. The research is based on sharia economic cases that have been decided in the last fifteen years and interviews with some judges, advocates, and practitioners of sharia economy. The research findings showed that there are three key points on which public trust in religious courts remains low: (1) The historical development of religious courts and the incompleteness of laws and regulations to support the judicial process in resolving sharia economic disputes, (2) The business demand to deal with disputes effectively and efficiently as well as the factor of the lack of the supporting facilities and infrastructures; and (3) lack of legal literacy among Islamic economic practitioners to resolve disputes. Public trusts are crucial for Muslims to raise awareness and belief in the religious court. This macroscopic study requires microscopic analysis to see the anatomy of public perception of religious courts in solving sharia economic disputes. Abstrak Peradilan Agama kurang dimanfaatkan untuk pencarian keadilan dalam sengketa ekonomi syariah. Mereka hanya memanfaatkan Peradilan Agama untuk memecahkan masalah dalam hukum keluarga seperti perceraian, sengketa kewarisan, permohonan hak asuh anak, wasiat dan hibah. Kecenderungan ini menjadi tanda dari rendahnya kepercayaan publik terhadap Peradilan Agama. Tulisan ini menganalisis bagaimana kepercayaan publik kepada Peradilan Agama menjadi kendala utama dalam pemanfaatan pelayanan untuk menyelesaikan sengketa ekonomi syariah. Fokus penelitian ini pada data perkara ekonomi syariah yang diputuskan pada lima belas tahun terakhir dan wawancara dengan sejumlah hakim, pengaraca, dan pelaku ekonomi syariah. Hasil penelitian menunjukkan bahwa tiga prasyarat yang menjadi dasar lemahnya kepercayaan publik terhadap Peradilan Agama: (1) sejarah perjalanan Peradilan Agama dan aturan perundang-undangan yang tidak lengkap untuk mendukung proses peradilan penyelesaian sengketa ekonomi syariah; (2) tuntutan budaya bisnis dalam penyelesaian sengketa yang cepat efektif dan efisien serta kurangnya sarana dan prasana pendukungnya serta; (3) literasi hukum yang rendah di kalangan pelaku ekonomi syariah untuk menyelesaikan sengketa syariah di Peradilan Agama. Kepercayaan publik menjadi sangat krusial bagi umat Islam dalam meningkatkan kesadaran dan kepercayaan pada lembaga Peradilan Agama. Tulisan ini bersifat umum sehingga dibutuhkan suatu kajian yang bersifat khusus untuk dapat melihat anatomi persepsi publik terhadap Peradilan Agama dalam penyelesaian sengketa ekonomi syariah.